Time and regional perspectives of food insecurity during the economic crisis in Portugal, 2011-2013 - Gregório, Maria João (2015)
Food insecurity (FI) has received much attention in recent years, even in high-income countries, due to the increasing trend of poverty and social inequalities indicators, as a result of the global financial crisis. The establishment of a monitoring system of FI becomes a priority for food and nutrition policies. Our study aims to evaluate FI trends during the economic crisis in Portugal and to identify regional disparities throughout the country. Data derived from three surveys conducted by the Portuguese Directorate-General of Health, concerning FI of the Portuguese population, during the period that Portugal was under the International Monetary Fund financial assistance program (2011–2013). Data were collected by face-to-face interviews and FI was evaluated using a psychometric scale. Logistic regression models were used to identify regional disparities in FI. The prevalence of FI was relatively unchanged at national and regional levels, during the analysis period. Data from 2013 indicates a high prevalence of FI (50.7%), including 33.4% for low FI, 10.1% for moderate FI and 7.2% for severe FI. Disparities according health region were also found for household FI. Algarve, Lisboa and Vale do Tejo were the two regions with the highest levels of FI, even after controlling for other socioeconomic variables. High levels of FI found in Portugal and the different regional profiles suggest the need for regional strategies, in particular in the most affected regions based on a broader action with different policy sectors (health, social security, municipalities and local institutions in the field of social economy).